Super-FRS Target Area Remote Handling: Scenario and Development. (12th November 2013) - Orona, Luis Miguel; Weick, Helmut; Mattila, Jouni; Amjad, Faraz; Kozlova, Ekaterina; Karagiannis, Christos; Behr, Karl-Heinz; Winkler, Martin
The Super-FRS, Superconducting Fragment Separator, is a unique machine that presents several challenging technical problems. One of these is regarding how to conduct maintenance in the target area where high levels of radiation will be generated and human access is forbidden. To address this problem the use of a remote maintenance system is foreseen. The objective of this paper is to develop a systems engineering (SE) research and development (R&D) approach suitable to develop the Super-FRS Target Area Remote Maintenance Systems (TARMS) and the RH design adaptation of the components in the target area. The Super-FRS target area is described in detail in order to introduce the need for a remote maintenance system. Components in the target area are classified by adopting ITER RH maintenance classification. The general scenario of remote handling and the current target area remote maintenance system are described. Finally, the proposed systems engineering approach is presented.